Analyzing K-11 Students' Boiling Conceptions with BFT-Test using Rasch Model: A Case Study in the COVID-19 Pandemic - Husnah, Ilma; Suhandi, Andi; Samsudin, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2020)
During the COVID-19 pandemic, students tend to have limitations that can cause them to experience misconceptions of teachers' concepts in an online setting. This becomes an insufficient basis for students to construct knowledge. Students can properly use one concept in a particular context and experience misconceptions on the same concept but in different contexts. This study aims to determine students' misconceptions about the concept of boiling, the percentage of misconceptions on each indicator of the boiling concept, and the causes of misconceptions in eleventh-grade (K-11) natural science students in one of the state high schools in Bandung Barat Regency. This study involved 92 students as samples in the study. The instrument used to analyze the concept of boiling misconceptions is the instrument was named BFT-Test (Boiling concept Four-tier). The misconceptions analysis of buffer solutions using the BFT-Test instrument showed that misconceptions occurred by 60 %, scientific conceptions by 13 %, and lack of knowledge by 27 %. Most misconceptions occur in analyzing the effects of pressure at the boiling point, which is 65 %. Based on this research results, the teachers are expected in the online learning process during the COVID-19 pandemic to link the material taught with concepts that exist in students' daily lives so that students easily capture the material and students remember the concepts in each given material.